Electromobility in India: attempts at leadership by businesses in a scant policy space - Ankur Chaudhary (Deutsches Institut für Entwicklungspolitik (DIE), 2014)
Electric vehicles are increasingly seen as a critical component of global climate change mitigation efforts. This view, coupled with the co-benefits of energy security, industrialization and job creation, among other things drives the response of various stakeholders. In a national framework – with linked factor and demand conditions – such responses are leading to the emergence of various national electromobility trajectories. Within these, the Indian case is unique in terms of its emerging automobile sector, energy security constraints and a weak innovation system in general. An interplay of policy, business strategy, technology competence and market forces is shaping the present nature as well as the future direction of the Indian trajectory. This paper presents three case studies in the Indian electromobility sector and uses the lessons learned from these cases to identify and analyse the key trends, both technological as well as organizational, that are shaping and emerging in this trajectory. The paper highlights attempts by Indian firms, made in spite of the absence of a strong policy push, at integrating electromobility in their business strategies and the resulting innovation system attributes.
Keywords: 330; Klimawandel; Technologie und Innovation